(untitled) (Olhar de Professor, 2022)
This article aims to reflect and discuss the scope of the actions developed by the Division of Teaching, Research, Extension and Service in Special Education - Depae, of the Federal University of Uberlândia, Campus Pontal, regarding the initial training of undergraduate students who participated in what was promoted by this division in the period from 2015 to 2020, who act/acted, directly or not, with the target population of special education. In this sense, the document analysis was based on some authors (MENDES, 2006; MICHELS, 2006, 2011; VAZ; MICHELS, 2017 and GLAT; ESTEF, 2021) and advising documents (BRAZIL, 2008; BRAZIL, 2015). It can be concluded that DEPAE/Pontal, even with obstacles, seeks to promote actions in this area of ​​inclusive education, contributing to the training of undergraduate students at the Pontal campus.